Mitigating food deserts: Do farmers' markets break from the status quo?. Issue 1 (March 2017) - Sage, Jeremy L.; McCracken, Vicki A.
Abstract: This paper revisits the previously developed rationale for periodic market placement under the contemporary lens of farmers' markets. The number average size rule is first employed to question whether the 'centre' level that can sustain a grocery store is climbing, and creating disadvantaged access. This is extended to the farmers' market system that is portrayed as an alternative ethic to the conventional system. This effort examines whether the discourse of local matches the actions, or whether farmers' markets location decisions mirror that of conventional distribution. The results from bivariate spatial point pattern analyses reinforce notions of the retail system, as leaving areas of effective food deserts, and further suggests farmers' markets have a tendency to locate close to those retail outlets.